Bi‐allelic mutations in MCIDAS and CCNO cause human infertility associated with abnormal gamete transport. Issue 6 (20th October 2021) - Ma, Cong; Wu, Huan; Zhu, Damin; Wang, Ying; Shen, Qunshan; Cheng, Huiru; Zhang, Junqiang; Geng, Hao; Liu, Yiyuan; He, Xiaojin; Tao, Fangbiao; Cao, Yunxia; et al.
Abstract: Reduced generation of multiple motile cilia (RGMC) and the consequent primary ciliary dyskinesia (PCD) cause infertility due to a substantial reduction in the number of multiciliated cells (MCCs) in the efferent ducts (EDs)/oviducts. MCIDAS acts upstream of CCNO to regulate the biogenesis of basal bodies (BBs); therefore, both genes play a vital role in the multiciliogenesis of the reproductive tract epithelium. In this study, whole‐exome sequencing was performed to identify the causative genes in 10 unrelated infertile patients with PCD: seven males and three females. Notably, homozygous frameshift mutations in MCIDAS (c.186dupT, p.Pro63Serfs*22) and CCNO (c.262_263insGGCCC, p.Gln88Argfs*8) were identified in one male and one female participant from two unrelated consanguineous families. Haematoxylin–eosin staining/scanning electron microscopy revealed abnormal MCCs in the mutated EDs/oviducts. Furthermore, transmission electron microscopy revealed significantly reduced BBs. Immunofluorescence staining showed the absence of MCIDAS and CCNO signals in the affected tissues and confirmed that MCIDAS acts upstream of CCNO in the context of multiciliogenesis in the reproductive tract epithelium. In vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) was successful, with a positive pregnancy outcome in both MCIDAS‐ and CCNO‐ mutated patients. Our results support the use of IVF/ICSI interventions to treat infertility due to RGMC in couples. Abstract : Theoretically, MCIDAS acts upstream of CCNO to regulate the biogenesis of multiple motile cilia of multiciliated cells. The homozygous frameshift mutations in MCIDAS (c.186dupT, p.Pro63Serfs*22) and CCNO (c.262_263insGGCCC, p.Gln88Argfs*8) were identified in two unrelated consanguineous families, respectively. And reduction in the number of multiciliated cells in the MCIDAS ‐mutated efferent ducts (EDs)/ CCNO ‐mutated oviducts lead to human infertility.